Market Capitalisation and Financial Performance: Evidence from Banking Listed Company in Indonesia - Anita Roosmawarni; Didin Fatihudin; Nurullaili Mauliddah (Universitas Muhammadiyah Magelang, 2022)
Market capitalization is a vital performance tool for the banking companies, the current profit and the future earnings of the banks also have an important impact on the market capitalization of the banks. This study aimed to determine Return on Equity effect, Capital Adequacy Ratio, Non Performing Loan and Firm Size on the banking sectors market capitalization listed on the Indonesia Stock Exchange 2010-2020. This research method used multiple linear regression analysis with data processing using the tools Stata 15 program. The sampling method of this research used a purposive sampling technique. The F-test results showed that simultaneously Return on Equity, Capital Adequacy Ratio, Non Performing Loan, and Firm Size had a significant effect on market capitalization with a significance value of 0,0%. The test results with the t-test show that Capital Adequacy Ratio and Firm Size has a significant positive effect on market capitalization with a significance level less than 0,0%.